Profile of the geriatric patient hospitalised at Universitas Hospital, South Africa - Anna M. van Staden; Dirk J.V. Weich (South African Family Practice)
Background: The elderly population in Africa is unevenly distributed across the continent, with the highest percentage of elderly living in the Southern African region. In 1996, the elderly population of South Africa (65 years and older) was roughly 6.7%, and was calculated to be 10.4% by 2025. If the latter expectation is anywhere near realistic, it stands to reason that the Department of Health should make timely provision for the care of these future patients, as the prevailing disease patterns within a population change as that population ages. Thus, there is an urgent need for profiles of elderly patients in order for adequate training to be implemented and for beds and equipment to be ready when needed.